Identification and Ranking of Key Performance Indicators in Building Construction Projects in Kenya - Mbugua, M.; Ajwang’, P. O.; Winja, M. M. O. (Engineering, Technology & Applied Science Research, 2021)
Building construction projects suffer from many dangers such as cost and time overruns. A major reason for the failure of such projects is the lack of measurements of the construction performance. There is usually a disparity of judgment among the stakeholders when it comes to the perception of failure and success of a building construction project because it is based on personal indices. The aim of this study is to identify and rank the key performance indicators in their relative importance as a way to assist in building construction performance. A thorough literature review was conducted and 10 key performance indicators were identified. A questionnaire survey and interviews were used to collect data and the results were analyzed using the analytical hierarchical process, pair-wise comparison. As a result, the highest prioritized key performance indicator was safety, followed by time effectiveness and client satisfaction. The least prioritized key performance indicator was the environmental performance. The results of this paper may serve as a guideline in improving building construction projects.